Particle migration in large cross-section ceramic on-demand extrusion components. Issue 3 (March 2023) - Martin, Austin J.; Li, Wenbin; Watts, Jeremy; Hilmas, Gregory E.; Leu, Ming C.; Huang, Tieshu
Abstract: Ceramic On-Demand Extrusion (CODE) is a direct ink writing process which allows for the creation of near theoretically dense ceramic components with large cross-sections due to oil-assisted drying. Yttria-stabilized zirconia (YSZ) colloidal pastes (∼d50 ≲ 1 µm) were used in CODE to produce dense (multi-road infill and ≳ 98% relative density), large continuous volume (> 1 cm 3 ), and high fidelity (nozzle diameters ≲ 1 mm) structural ceramic components. However, many of these printed components underwent significant particle migration after forming. The reason for this particle migration defect was investigated using the coffee-ring effect for dilute solutions and rheological methods for dense suspensions. Modifications to the colloidal paste, such as changes in solids loading, pH, or surfactant concentration were explored as to their effectiveness to mitigate the defect. Ultimately, paste formulation and printing trade-offs are discussed with respect to the post-printing defect and as to general direct-write patterning.